PENYELENGGARAAN PROGRAM SD-SMP SATU ATAP PADA DAERAH TERPENCIL DALAM LATAR BUDAYA RUMAH BETANG KALIMANTAN TENGAH - Hasan, Rudi (Equity In Education Journal, 2019)
Abstract: The purpose of this study is to describe the implementation of the One-Roof Junior Secondary School as an alternative to the distribution of nine-year basic education in remote areas in the cultural setting of Central Kalimantan Betang Houses. This research is a qualitative research with a multi-site study design on 3 One-Roof Junior Secondary Schools in Gunung Mas Regency. Data collection is done by methods: in-depth interviews (indepth interview), participant observation (participant observation), and study documentation (study of document). Determination of data sources is done by using purposive sampling technique. Data analysis is done through the activities of organizing data, organizing and dividing data into units that can be managed, mensiteis, looking for patterns, find what is meaningful and what is researched to be decided and reported systematically (Bogdan and Biklen, 1998). Data analysis in this research was carried out in two stages, namely: data analysis for each site (single site) and cross-site data analysis. Checking the validity of the data is done by using a degree of credibility through both source and method triangulation techniques. The results of the study found that the values of the betang house culture that underlies the implementation of the One-Roof Junior Secondary School appeared on: (1) bureaucratic structure, including: SOP, coordination and empowerment of HR; (2) resources, including: human resources, infrastructure and financing; and (3) communication, including: internal communication, with supporting elementary schools, with related agencies, and the community around the school. Keywords: One-Roof Junior Secondary School, Remote Area, Betang House Culture Abstrak: Tujuan penelitian ini adalah mendeskripsikan penyelenggaraan program SD-SMP Satu Atap sebagai alternatif pemerataan pendidikan dasar sembilan tahun pada daerah terpencil dalam latar budaya rumah betang Kalimantan Tengah. Penelitian ini merupakan penelitian kualitatif dengan rancangan studi multi situs pada 3 SMPN Satu Atap di wilayah Kabupaten Gunung Mas. Pengumpulan data dilakukan dengan metode: wawancara mendalam (indepth interview), observasi partisipan (participant observation), dan studi dokumentasi (study of document). Penetapan sumber data dilakukan dengan teknik purposive sampling. Analisis data dilakukan melalui kegiatan mengorganisasi data, menata dan membagi data dalam unit-unit yang dapat dikelola, mensitesis, mencari pola, menemukan apa yang bermakna dan apa yang diteliti untuk diputuskan dan dilaporkan dengan sistematis (Bogdan dan Biklen, 1998). Analisis data dalam penelitian ini dilakukan dalam dua tahap, yaitu: analisis data tiap situs (situs tunggal) dan analisis data lintas situs. Pengecekan keabsahan data dilakukan dengan menggunakan derajat kepercayaan (credibility) melalui teknik triangulasi baik sumber maupun metode. Hasil penelitian menemukan bahwa nilai-nilai budaya rumah betang yang mendasari dalam penyelenggaraan SD-SMP Satu Atap muncul pada: (1) struktur birokrasi, meliputi: SOP, koordinasi dan pemberdayaan SDM; (2) sumberdaya, meliputi: SDM, sarana prasarana dan pembiayaan; dan (3) komunikasi, meliputi: komunikasi intern, dengan SD penyangga, dengan dinas terkait, dan masyarakat sekitar sekolah. Kata Kunci: SD-SMP Satu Atap, Daerah Terpencil, Budaya Rumah Betang References: Arikunto, S. (1998). Prosedur Penelitian: SuatuPendekatan Praktek. Jakarta: Rineka Cipta. Ary, D., Jacobs, L. C., & Razavieh, A.(2002). Introduction to Research in Education. Sixth Ed. Belmont, CA: Wadswort. Thomson Learning. Bogdan, R. C.,& Biklen, S.K.(1998). Qualitative Research For Educatio: An Introduction to Theory and Methods.Third Ed. Boston: Allyn and Bacon. Bollen, R. (1997). Making Good Schools: Linking School Effectiveness and School Improvement. London and New York: Routledge. Brienkerhoof, D. W.,& Crosby, L.B. (2002). Managing Policy Reform: Concept and Tool for Decision-Makers in Developing and Transitionong Countries. United States of America: Kumarian Perss, Inc. Castetter, W.B. (1996). The Human Resources Function in Educational Administration (Sixth Edition). New Jersey: Prentice Hall, Inc. Dunn, W. N. (1981). Public Policy Analysis: An Introduction. Englewood: Cliff, N.J. Prentice, Inc. Dwijowijoto, R. N. (2004). Komunikasi Pemerintahan. Jakarta: Elek Media Komputindo Kelompok Gramedia. Edward, G. (1980). Implementing Public Policy. Washington, DC. Congressional Quarterly, Inc. Glickman, C. D., Gordon, S. P., & Ross-Gordon, J. M. (2009). The Basic to Supervision and Instructional Leadership. Secon Ed, Boston: Pearson. Koehler. (1981). Organizational Communication, Behavioral Perspective. New York: Holt, Rinehart and Winston. Kratzer. (1996). Marketing the Nation. New York: Free Press. Kusni. J. J. (2006). Pergulatan Identitas Dayak Dan Indonesia: Belajar dari Tjilik RiwutPalangka Raya: Penerbit Galangpress. Mantja, W. (2002). Manajemen Pendidikan dan Supervisi Pengajaran (Kumpulan Karya Tulis Terpublikasi). Malang: Wineka Media. Mantja, W. (2008). Ethnography, Desain Penelitian Manajemen Pendidikan. Malang: Elang Mas. Nasution, S. (1998). Metode Penelitian Naturalistik Kualitatif Bandung: Transito. Peraturan Pemerintah RI Nomor47 Tahun 2008. Wajib Belajar. Bandung: Penerbit Citra Umbara. Robbins, S., P. (1998). Organizational Behavior. New Jersey: Englewood Cliffs. Sonhadji. K. H. A. (1996). Teknik Pengumpulam Data dan Analisis Data dalam Penelitian Kualitatif dalam Arifin. Penelitian Kualitatif. Malang: Kalimasahda Press. Sugiyono. (2006). Metode Penelitian Administrasi. Bandung: Alfabeta. Undang-Undang Dasar Republik Indonesia Tahun1945. Bandung: Penerbit Citra Umbara. Undang-Undang Republik Indonesia Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional. 2006. Bandung: Pcnerbit Citra Umbara. Usop, K. M.A.(1994). Pakat Dayak: Sejarah Integrasi dan Jati Diri Masyarakat Dayak dan Daerah Kalimantan Tengah. Palangka Raya: Yayasan Dikbud Batang Garing. Winarno, B. (2002). Kebijakan Publik: Teori dan Proses. Yogyakarta: Media Pressindo.